Volar Scaphoid Plating for Nonunion: A Multicenter Case Series Study - Eng, Kevin; Gill, Stephen; Hoy, Simon; Shridar, Vivek; Van Zyl, Natasha; Page, Richard (Journal of Wrist Surgery, 2020)
Background The volar scaphoid plate from Medartis (Medartis AG, Austrasse, Basel, Switzerland) is a variable angle titanium locking plate, preformed for the volar aspect of the scaphoid. It does not have compressive capability, and may act as a bridging device. It may provide an advantage over a compression screw where the pathoanatomy is less favorable to such a device with increased rotational stability. It may act as a buttress plate for correction of humpback deformity for example. It has been used in nonunions and with vascularized grafts.Questions Our study aims to assess the results of our patients with scaphoid nonunion treated with scaphoid volar plating over a larger number of patients. We aim to identify techniques to increase the success of plating.Methods Patients from our cohort were retrospectively reviewed. Operations were performed by three hand fellowship trained surgeons and in two centers. Inclusion involved a scaphoid plate procedure for a nonunion of the scaphoid with a minimum of 6 months of follow-up. Exclusions were those who had less than 6 months of follow-up. Data included demographics, patient-rated wrist evaluation (PRWE), a quick disabilities of the arm, shoulder, and hand (qDASH), visual analogue score, and range and grip. Radiology was reviewed.Results Thirty-two eligible patients were assessed. The mean age was 25 years (range 13–46), 2 were female and 15 were smokers. Mean follow-up postsurgery was 18 months. Twenty-nine of 32 patients united (90.6%) on computed tomography scan. Clinical assessment was performed in the 25 patients. The mean qDASH score was 12.5 (range 0–42) and mean PRWE was 11 (range 0–54). The mean arc of motion was 115 degrees. The mean grip strength was 39 kg compared with 41 kg on the nonoperated side.Conclusion We postulate that the plate acts like an internal bridging device, acting over a small distance, and inherent stability of the construct with structural graft and accurate reduction prior to plating is advantageous. Potential problems include plate impingement on the volar lip of the radius, particularly when trying to plate more proximal fractures. Ideally, it is utilized for mid to distal waist fractures.
Keywords: scaphoid; nonunion; plate fixation; bone grafting